SELF-IDENTIFICATION AMONG GRIEVING PRIMARY SCHOOL CHILDREN AS THE FACTOR OF THEIR SOCIALIZATION - Butvilas, Tomas (Acta Paedagogica Vilnensia, 2008)
Relation between loss in the family and child‘s socialization is stressed in many psychological and educational works Experienced loss is a very difficult matter for a child, who tries to internalize his/her family‘s traditions, values and also to form his/her identity – self I. Self identification in this article is mostly defined as a specific feature of children (age 7–11). On the one part it is self identification with other people, their groups, and satisfying the need to belong to some of those social groups on the emotional basis. On the other part it is quite a complicated psychological phenomenon, which helps to take some other person’s characteristics and perceive them as one’s own. The social interactions with others, especially with family members, is an important component of children’s identification to whom and also forming their self I. In other words, through membership the self-awareness and social identities are created, and also that reveals the individuality of a child’s interaction with him/herself and with others. It was stated that experienced loss in the family negatively affects self-identification processes: grieving children have more negative attitudes towards their home and parents, and also they do not feel so good while being at home. Besides, these children have also more negative than positive attitude towards school and their own status among peers (they have pointed out that nobody misses them when they are not in class, that they have no one to share their sadness or happiness with etc.). All that negatively affects these children’s openness, self-confidence, and self-control. The experienced loss has many negative effects on grieving children’s attitude towards themselves (they tend to think as having no friends at school, that it is difficult for them to find some new friends etc.).